THE INNOVATIVE COMPOSITE MATERIALS IN CONSTRUCTION - Galina Mikhailovna Danilova-Volkovskaya; Valery Yurievna Shimlovskaya; Nikodim Nikolaevych Volkovskiy (Современная наука и инновации, 2022)
The article describes the desirability of the composites based on polypropylene and natural fillers, for use as building materials. The results of the study of the mechanical properties of composites.